Impact of Letermovir Primary Cytomegalovirus Prophylaxis on 1-Year Mortality After Allogeneic Hematopoietic Cell Transplantation: A Retrospective Cohort Study . (3rd January 2022) - Su, Yiqi; Stern, Anat; Karantoni, Eleni; Nawar, Tamara; Han, Gyuri; Zavras, Phaedon; Dumke, Henry; Cho, Christina; Tamari, Roni; Shaffer, Brian; Giralt, Sergio; Jakubowski, Ann; et al.
Abstract: Background: Cytomegalovirus (CMV)–seropositive (R + ) hematopoietic cell transplant (HCT) recipients have a survival disparity compared with CMV-seronegative recipient/donor (R – D – ) pairs. We hypothesized that primary letermovir prophylaxis (LET) may abrogate this disparity. We investigated the relationship between LET and mortality at 1 year post-HCT. Methods: In this retrospective cohort study, we included adult R – D – or R + patients who received HCT pre-LET (between 1 January 2013 through 15 December 2017) and post-LET (between 16 December 2017 through December 2019). R + were categorized by LET receipt as R + /LET or R + /no-LET. Cox proportional hazard models were used to estimate the association of LET with all-cause mortality at 1 year after transplantation. Results: Of 848 patients analyzed, 305 were R – D –, 364 R + /no-LET, and 160 R + /LET. Because of similar mortality (adjusted hazard ratio [aHR], 1.29 [95% confidence interval CI, .76–2.18]; P = .353]) between pre-LET/R – D – and post-LET/R – D –, R – D – were combined into 1 group. Compared with R – D –, the aHR for mortality was 1.40 (95% CI, 1.01–1.93) for R + /no-LET and 0.89 (95% CI, .57–1.41) for R + /LET. Among R +, LET was associated with decreased risk of death (aHR, 0.62 [95% CI, .40–.98]); when conventional HCT and T-cell depleted HCT were analyzed separately, the aHR was 0.86 (95% CI, .51–1.43) and 0.21 (95% CI, .07–.65), respectively. Conclusions: At 1 year post-HCT, LET was associated with closing the mortality disparity between R – D – and R + . Among all R +, LET was associated with decreased mortality, driven by 79% reduced incidence of death in T-cell depleted HCT. Abstract : At 1 year after hematopoietic cell transplant (HCT), letermovir prophylaxis (LET) was associated with closing the mortality disparity between cytomegalovirus R – D – and R + . Among all R +, LET was associated with decreased mortality; driven by 79% reduced incidence of death in T-cell–depleted HCT.